Long-term experience with onabotulinumtoxinA in the treatment of chronic migraine: What happens after one year?. (September 2015) - Cernuda-Morollón, Eva; Ramón, César; Larrosa, Davinia; Alvarez, Rocío; Riesco, Nuria; Pascual, Julio
Background: OnabotulinumtoxinA (onabotA) has shown its efficacy over placebo in chronic migraine (CM), but clinical trials lasted only up to one year. Objective: The objective of this article is to analyse our experience with onabotA treatment of CM, paying special attention to what happens after one year. Patients and methods: We reviewed the charts of patients with CM on onabotA. Patients were injected quarterly during the first year but the fifth appointment was delayed to the fourth month to explore the need for further injections. Results: We treated 132 CM patients (mean age 47 years; 119 women). A total of 108 (81.8%) showed response during the first year. Adverse events, always transient and mild-moderate, were seen in 19 (14.4%) patients during the first year; two showed frontotemporal muscle atrophy after being treated for more than five years. The mean number of treatments was 7.7 (limits 2–29). Among those 108 patients with treatment longer than one year, 49 (45.4%) worsened prior to the next treatment, which obliged us to return to quarterly injections and injections were stopped in 14: in 10 (9.3%) due to a lack of response and in four due to the disappearance of attacks. In responders, after an average of two years of treatment, consumption of any acute medication was reduced by 53% (62.5% in triptan overusers) and emergency visits decreased 61%. Conclusions: Our results confirm the long-term response to onabotA in three-quarters of CM patients. After one year, lack of response occurs in about one out of 10 patients and injections can be delayed, but not stopped, to four months in around 40% of patients. Except for local muscle atrophy in two cases treated more than five years, adverse events are comparable to those already described in short-term clinical trials.